PEMODELAN STRUKTUR PADA LAPANGAN WAHRE, CEKUNGAN MADURA, JAWA TIMUR UNTUK PERHITUNGAN CADANGAN AWAL GAS (GAS INITIAL IN PLACE) - Restuwaty Indra Wahyuni; Muhammad Irham Nurwidiyanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Seismic interpretation has been done in Wahre field, Madura Basin, East Java with the main target of the research is Mundu Formation, which is the existence of gas. The research aim to modeling the depth structure to estimate the initial gas reserves. Modeling of the structure obtained from the results of time domain conversion (TWT) to the depth domain (Feet). Depth modeling was obtained from the results of linier regression of uncertainity graph two well log that have different depth. The depth structure shows the location of Mundu Formation are crossways from the west sea to the southeast as the background of the geological of Madura Basin. The linier regression uncertainity result represent the value of GRV (gross rock volume) which is divided into three case. The first value is high case, the high case is 65.505.181 m3. Mid case or medium case is 65.446.249 m3. And psimis case is 58.060.543 m. The three GRV value will be used to calculate the approximate initial gas in place (GIIP). GIIP results was 64.7 BCF to high case. The medium case was 64,6 BCF. And for the psimis case was 57,3 BCF.